EFFECTS OF ALUM APPLICATION AND WATER QUALITY ON SOME PROPERTIES IN DEGRADED SOIL AND YIELD OF SORGHUM (Sorghum bicolor L.) - Obaid, T. K.; Shamsullah, J. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Soil degradation and water scarcity are considered the main challenges that are faced the agricultural production, particularly with changing climate. The objective of this study was to study the effectiveness of alum in improving some soil chemical properties using two qualities of irrigation water . The experimental study was conducted in the Anbar Governorate / Al-Khayrat district in the fall season in degraded clay loam soil. The experimental design for the study site was the split- Block arrangement with a randomized complete block design (RCBD) with three replicates. This study included two factors: the main factor was water quality with river water (1.8 dS m-1) and well water (3.8 dS m-1), and the secondery factor was alum application with eight levels (0, 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, and 1.4 %) based on dry soil. The results showed that pH, EC were decreased by 12.7, 65.1%, respectively when applied 0.8% of alum at the irrigation of river water and decreased by 11.9, 61.4 %, respectively when applied 1.0% of alum at irrigation with well water as compared to control treatment. While an increase occurred in CEC of about 20.0 and 19.8% at the irrigation of river and well water, respectively as compared to control treatment.While the addition of all levels of aluminum sulfate (alum) led to a significant effect on the available nitrogen in the soil and the biological yield when treating alum a5, which reached 48.6% and 48.50, respectively.